(untitled) (Journal of actual problems of jurisprudence, 2019)
The article deals with the present status of the Law of the sea. The author analyses in detail the basic principles and multilateral intergovernmental agreements that regulate the activities on the sea and the adjacent areas. The classi fi cation of major principles is offered for the readers. Possible future perspectives of development in this area are offered for the readers. Regional aspects of the Law of the sea are mentioned in the work. The article also touches on the issues of the Caspian sea status. Some agreements in that fi eld are considered in more detail. The positions of littoral countries is scrutinized as well.